Study of The Soft Skills Development in The Framework Of The Activities Of Student Communities - Kolchina, Vera Viktorovna (2021)
The article presents the results of a study of the Soft Skills development in the activities of student societies. The purpose of the article is the theoretical and empirical study of the Soft Skills development in the activities of student societies. The research methodology and its algorithm were selected due to the purpose of the study. To solve the research questions posed, we compiled a list of student societies of the Mytischi Branch (MB) of the Bauman Moscow State Technical University. It included 87 student societies, which were classified according to the type of their activity. The hypothesis of the research is that a close connection between student societies stimulates members of one society to be interested in the activities of associate societies, thereby acquiring new skills within the framework of this activity, among which there are so-called Soft Skills. Student societies can form both general, characteristic of all student organizations, and specific skills, characteristic of certain types of activity. In the course of the research work, all possible student societies were identified and classified. Next, we built a network map of the interaction among student societies. Also, using a targeted sample, 9 student societies were selected, representing different fields of activity. The leaders of these societies were interviewed using a semi-formalized interview method. The statutory documents on the activities of the societies under consideration were analyzed using the traditional method of document analysis.